Effects of white matter hyperintensities, neuropsychiatric symptoms, and cognition on activities of daily living: Differences between Alzheimer's disease and dementia with Lewy bodies. Issue 1 (2nd May 2022) - Mirza, Saira Saeed; Saeed, Usman; Ramirez, Joel; Herrmann, Nathan; Stuss, Donald T.; Black, Sandra E.; Masellis, Mario
Abstract: Introduction: Disability is common across Alzheimer's disease (AD) and dementia with Lewy bodies (DLB). White matter hyperintensities (WMHs) are prevalent in both diagnoses and associated with disability; both diagnoses show neuropsychiatric symptoms (NPS) and impaired cognition. Methods: In AD and DLB, we examined if WMHs, NPS, and cognition associate with basic and/or instrumental activities of daily living (BADLs and/or IADLs) cross‐sectionally, and longitudinally over ≈1.4 years. Results: Across both diagnoses, NPS were not only associated with greater disability in performing both BADLs and IADLs, but were also associated with a decline in the ability to perform BADLs in the AD group. In the DLB group only, higher WMH volume was associated with greater disability in performing both BADLs and IADLs, and was associated with a decline in the ability to perform BADL over time. Discussion: Management of NPS and WMHs, particularly in DLB, might help maintain functionality in dementia patients for longer.